Studies on Residual Hydrocyanic Acid (HCN) in Garri Flour Made from Cassava (Manihot Spp.) - Odoemelam, S.A. (Pakistan Journal of Nutrition, 2005)
Garri flour was produced from mashed cassava ( Manihot spp ) roots, which had been subjected to fermentation for time periods of between 6 and 72 h. The hydrocyanic acid content of each batch was estimated by spectrophotometric alkaline picrate method. White and yellow garri flour samples procured from markets in Abia State, Nigeria were also analyzed for their HCN contents using the above-mentioned method. The HCN content decreased significantly with the length of fermentation period of the grated cassava mash. Levels of residual HCN were also significantly influenced by the source and type of garri flour (whether white or yellow). The white garri flour had higher HCN levels than the yellow.